Ethics Hype? - Caulfield, Timothy (The Hastings Center report, 2016)
There has been growing concern about the phenomenon of science hype, the tendency to exaggerate the value or near-future application of research results. Although this is a problem that touches every area of biomedicine, the topic of genetics seems to be particularly prone to enthusiastic predictions. The world has been told for over two decades-by the media, researchers, politicians, and the biotech industry-that a genome-driven health care revolution is just around the corner. And while the revolution never seems to arrive, the hopeful rhetoric continues. It has been suggested that this unrelenting “genohype” is having a range of adverse social consequences, including misleading the public and hurting the long-term legitimacy of the field. While we need more good data on the nature and magnitude of these possible harms, few would argue with the proposition that sustained science hype is a bad thing. We all benefit from robust science and accurate public representations of biomedical research. But, to date, there has been very little consideration of the degree to which the scholarship on the related ethical, legal, and social issues has been hyped. Are the conclusions from ELSI scholarship also exaggerated?